Impact of Advanced Practice Provider Integration into Multispecialty Group Practices on Outcomes Following Major Surgery. (February 2022) - Lai, Lillian Y.; Kaufman, Samuel R.; Modi, Parth K.; Ellimoottil, Chad; Oerline, Mary; Caram, Megan E.V.; Hollenbeck, Brent K.; Shahinian, Vahakn B.
Background . While advanced practice providers (APPs) are increasingly integrated into care delivery models, little is known about their impact in surgical settings. Given that many patients undergo surgery in multispecialty group practice settings, we examined the impact of APP integration into such practices on outcomes after major surgery. Methods . We used a 20% sample of national Medicare claims to identify 190 101 patients who underwent 1 of 4 major surgeries (coronary artery bypass graft [CABG], colectomy, major joint replacement, and cystectomy) at multispecialty group practices from 2010 through 2016. The level of APP integration was measured as the ratio of APPs to physicians within each practice. Rates of mortality, major complications, and readmission within 30 days of discharge after the index surgery were compared between patients treated in practices with low, medium, and high levels of APP integration using multivariable regression analysis. Results . Relative to patients treated in practices with low APP integration, those treated in practices with medium or high APP integration had significantly lower rates of mortality (2.4% [low integration] vs 1.9% [medium integration] vs 2.0% [high integration]; P < .01), major complications (34.1% [low] vs 31.2% [medium] vs 30.2% [high]; P < .01), and readmission (11.7% [low] vs 10.6% [medium] vs 10.1% [high]; P < .01). This relationship was consistent for virtually all outcomes when considering each surgery type individually. Conclusions . Integration of APPs into multispecialty group practices was associated with improved postoperative outcomes after major surgery. Future research should identify the mechanisms by which APPs improve outcomes to inform optimal utilization.